What is the Essence of Hypnosis?. Issue 2 (3rd April 2017) - Dell, Paul F.
Abstract: The author explores the nature of hypnosis, which he characterizes as a motivated mode of neural functioning that enables most humans to alter, to varying degrees, their experience of body, self, actions, and world. The essence of hypnosis is not to be found in hetero-hypnosis; instead, it lies in the spontaneous self-activation of that mode of neural functioning. The hypnosis field has substantially lost sight of spontaneous self-activation, because the word hypnosis is usually used to mean hetero-hypnosis . Self-activation of this mode of neural functioning is the necessary sine qua non of hypnotic psychopathology. Moreover, self-activation of trance is the characteristic hypnotic behavior of a distinct subset of highly hypnotizable individuals.